Optimizing the Management of Cancer Patients Treated With Systemic Therapies During the COVID-19 Pandemic: The New Role of PCR and CT Scan - Viansone, Alessandro A.; Ammari, Samy; Dercle, Laurent; Arnedos, Monica (Frontiers in Oncology, 2021)
In late 2019 and early 2020, the world witnessed the outbreak of the SARS-CoV-2 (also referred as COVID-19) in Wuhan, China. Its rapid expansion worldwide and its contagiousness rate have forced the activation of several measures to contain the pandemic, mostly through confinement and identification of infected patients and potential contacts by testing.